2015
DOI: 10.1002/ccd.25860
|View full text |Cite
|
Sign up to set email alerts
|

Association of mean platelet volume with angiographic thrombus burden and short‐term mortality in patients with ST‐segment elevation myocardial infarction undergoing primary percutaneous coronary intervention

Abstract: Increased MPV at admission is an independent predictor of large intracoronary thrombus burden and short-term mortality. It may be a useful biomarker for risk stratification in patients with STEMI undergoing primary PCI. © 2015 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 37 publications
3
17
1
1
Order By: Relevance
“…30) Although the pooled analysis of four ISAR trials 19) and a subgroup analysis of the CADILLAC trial 18) confirmed that a higher baseline PC was a predictor of adverse prognosis in patients undergoing PCI, other studies found no significant association between baseline PC and adverse prognosis in patients with STEMI undergoing PCI. [11][12][13][14]22) Our study confirmed again that high MPV was an independent predictor of adverse prognosis for patients with STEMI undergoing P-PCI, but high PC was not.…”
Section: Mpv/pc Ratio Predicate Prognosis In Stemisupporting
confidence: 65%
See 2 more Smart Citations
“…30) Although the pooled analysis of four ISAR trials 19) and a subgroup analysis of the CADILLAC trial 18) confirmed that a higher baseline PC was a predictor of adverse prognosis in patients undergoing PCI, other studies found no significant association between baseline PC and adverse prognosis in patients with STEMI undergoing PCI. [11][12][13][14]22) Our study confirmed again that high MPV was an independent predictor of adverse prognosis for patients with STEMI undergoing P-PCI, but high PC was not.…”
Section: Mpv/pc Ratio Predicate Prognosis In Stemisupporting
confidence: 65%
“…15) They noted that MPV was a strong, independent predictor of impaired angiographic reperfusion and 6-month mortality in patients with STEMI undergoing PCI. 15) This observation has since been confirmed by several other studies [10][11][12][13][14]16,17) and has been extended by the observation that elevated MPV at admission was an independent predictor of large intracoronary thrombus burden.…”
Section: Mpv/pc Ratio Predicate Prognosis In Stemimentioning
confidence: 56%
See 1 more Smart Citation
“…There has been rapidly growing interest in the association between MPV and the risk of cardiovascular events following STEMI. High MPV is an independent predictor of large intracoronary thrombus burden and short-term mortality in STEMI patients (Lai et al, 2015). Also, it is associated with lower ST-segment resolution and higher prevalence of major adverse cardiac events in patients receiving thrombolytic therapy for first time STEMI (Ghaffari et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…[29,31]. После публикации последне-го метаанализа в 2015 г. появилось еще не-сколько работ, подтверждающих прогностичес-кую значимость СОТ у больных с ОКС [32,41,42]. По крайней мере, в одном исследовании была выявлена корреляция СОТ с риском тромбо-зов после ЧКВ у больных со стабильной ИБС [43].…”
Section: средний объем тромбоцитов у больных с сердечно-сосудистыми пunclassified